Translation and validation study of the Malaysian version of the childbirth experience questionnaire - CEQ - Al-Kubaisi, Muna Khaleel Dheyab; Al-Ani, Ali Sabri Radeef (Ektodermal Displazi Grubu - Türkiye, 2018)
Establishing maternity services in a medical institution needs to be monitored to target client satisfaction which can be implemented by using a validated questionnaire such as the Childbirth Experience Questionnaire (CEQ). The objective of this study is to translate the English version of CEQ into Malay language; Bahasa Malaysia (BM) and to validate this Malaysian version. Two forward and backward translations were done in BM in accordance to guideline, and its validation was determined by using confirmatory factor analysis. A total of 400 pregnant women presented for labour at the Hospital Tengku Ampuan Afzan, Pahang state, Malaysia were approached to represent Malaysian population for reliability and validity purposes. Reliability of Malaysian Childbirth Experience Questionnaire revealed good Cronbach’s alpha value of 0.70. Construct validity, evaluated using exploratory factor analysis, had good factor loadings most of its items except 2 out of 22 items. The Malaysian Childbirth Experience Questionnaire had good psychometric properties among the tested population. Further studies are needed to verify these preliminary outcomes especially for higher analysis such Confirmatory factor analysis to affirm the validity among Malaysian population.